2013
DOI: 10.1080/19359705.2013.833882
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Mental Health Among Sexual Minority College Students: The Type and Form of Discrimination Does Matter

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 43 publications
4
141
0
5
Order By: Relevance
“…At the bivariate level, significant moderate correlations (not reported) were found between each form of discrimination and each outcome in the anticipated direction; the regression models similarly demonstrated that victimization and microaggressions related to greater forms of psychological distress (lower self-esteem; greater perceived stress and anxiety symptoms). These findings are in line with previous research looking at multivariate relationships between victimization and/or microaggressions and well-being (Silverschanz et al, 2008;Woodford et al, 2012;Woodford, Han et al, 2014;Woodford, Kulick et al, 2014). The documented significant positive relationships between microaggressions, self-esteem, perceived stress, and anxiety likely reflect the stressors inherent within microaggressions.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…At the bivariate level, significant moderate correlations (not reported) were found between each form of discrimination and each outcome in the anticipated direction; the regression models similarly demonstrated that victimization and microaggressions related to greater forms of psychological distress (lower self-esteem; greater perceived stress and anxiety symptoms). These findings are in line with previous research looking at multivariate relationships between victimization and/or microaggressions and well-being (Silverschanz et al, 2008;Woodford et al, 2012;Woodford, Han et al, 2014;Woodford, Kulick et al, 2014). The documented significant positive relationships between microaggressions, self-esteem, perceived stress, and anxiety likely reflect the stressors inherent within microaggressions.…”
Section: Discussionsupporting
confidence: 81%
“…Due to the prevalence of microaggressions and other subtle manifestations of discrimination as a more "acceptable" way of expressing prejudice in today's world (Woodford, Han et al, 2014), LGBTQ students, regardless of gender identity, may regularly feel the impact of microaggressions on their self-esteem, stress, and anxiety such that there is no differentiation in these relationships among these subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Au Canada comme aux États-Unis, la santé mentale des personnes LGBT semble être moins bonne que celles des personnes hétérosexuelles selon plusieurs études population-nelles (Chamberland, Beaulieu-Prévost, Julien, N'Bourké et de Pierrepont, 2011 ;Tjepkema, 2008). Or, de plus en plus de recherches lient l'état de la santé mentale des MSG à leurs expériences de discrimination (Burgess, Lee, Tran et van Ryn, 2007 ;Chae et al, 2010 ;Eaton, 2014 ;Frost et LeBlanc, 2014 ;Morrison, 2011 ;Woodford, Han, Craig, Lim et Matney, 2014). Par ailleurs, diverses études se sont penchées sur l'existence de telles discriminations dans la sphère du travail, parmi lesquelles certaines en examinent les conséquences sur la santé mentale.…”
Section: Introductionunclassified
“…Woodford and colleagues (2014b) found that 36% of lesbian, gay, bisexual, or queer (LGBQ) college students had experienced sexual orientation-related victimization, such as verbal or physical assaults, but LGBQ students are 17 times more likely to endure verbal derogation than a physical attack (Rankin et al, 2010). Encounters with campus homophobia leads to anxiety and depression among sexual minority college students compared to heterosexual students (Woodford, Han, Craig, Lim, & Matney, 2014a).…”
Section: Runaway and Homeless Lgbt Youthmentioning
confidence: 99%